2016
DOI: 10.1016/j.contraception.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraception among electronic cigarette users and cardiovascular risk: a systematic review

Abstract: Background: Women who use combined hormonal contraceptives and cigarettes have an increased risk for cardiovascular (CV) events. We reviewed the literature to determine whether women who use hormonal contraceptives (HC) and electronic cigarettes (e-cigarettes) also have an increased risk. Study Design: Systematic review. Methods: We searched for articles reporting myocardial infarction (MI), stroke, venous thromboembolism, peripheral arterial disease or changes to CV markers in women using e-cigarettes and HC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
0
8
0
1
Order By: Relevance
“…For instance, oxidative stress, cytotoxicity, and cardiomyocyte dysfunction are established effects of EVC [33]. Second, EVC impact adversely on BP management, cause tachycardia, and worsen arterial stiffness [19,34]. Third, EVC use has been associated with an increased risk of adverse clinical events, including atrial fibrillation and myocardial infarction, even if the causal link is still debated [24,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, oxidative stress, cytotoxicity, and cardiomyocyte dysfunction are established effects of EVC [33]. Second, EVC impact adversely on BP management, cause tachycardia, and worsen arterial stiffness [19,34]. Third, EVC use has been associated with an increased risk of adverse clinical events, including atrial fibrillation and myocardial infarction, even if the causal link is still debated [24,35].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Riley et al conducted a systematic review originally focused on the interplay between hormonal contraception, EVC, and cardiovascular risk [19]. No study explicitly focused on hormonal contraception was retrieved, and thus they expanded their analysis to the pathophysiologic link between EVC and cardiovascular outcomes.…”
Section: Recent Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…(33, 34) Studies of more advanced devices with effective nicotine delivery find that e-cigarette use produces the expected heart rate acceleration similar to that seen with cigarette smoking. Blood pressure effects are variable.…”
Section: Cardiovascular Toxicity Of Electronic Cigarettesmentioning
confidence: 98%
“…Any variability in effects across studies is likely to be related to differences in device-specific delivery of nicotine. ECs can cause an acute increase in heart rate, although the extent of this increase varies between studies 80 . In addition, numerous EC studies have also reported an acute increase in blood pressure among users 45,81–83 .…”
Section: Cardiovascular Toxicity Of Ecsmentioning
confidence: 99%